ChemInform Abstract: Synthesis of Polynitrostilbenes from 2, 4, 6‐Trinitro‐m‐xylene and 2, 4, 6‐Trinitrotoluene by a Microwave‐Assisted Solvent Free Method. Issue 42 (14th October 2014) - Xu, Junhui; Li, Fangmei; Wei, Jianping; Peng, Xinhua
Abstract Polynitrostilbenes are prepared from 2, 4, 6‐trinitro‐m‐xylene and 2, 4, 6‐trinitrotoluene by a microwave‐assisted solvent‐free method.